2015 IEEE International Symposium on Mixed and Augmented Reality Workshops 2015
DOI: 10.1109/ismarw.2015.13
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining and Enhancing Human-Surrogate Presence in Augmented Reality

Abstract: We present some background and ideas related to a human's sense of presence with a human surrogate (a stand-in for a human) in an augmented reality (AR) setting. In particular we examine several factors related to human surrogates that are common to robotics, virtual reality, and augmented reality; and some challenges that are unique to AR. We then discuss the roles of surrogate characteristics and behaviors in maintaining and perhaps enhancing a sense of presence with a surrogate. We conclude by sharing some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A virtual human can ask or suggest the user to turn on the light or to move a real object in their proximity so that they can perform a task more plausibly. As mentioned in [44], it can do so without revealing its functional deficiency. In that paper, a distinction is made between a virtual human's basic sensing that focuses on situationally and socially appropriate verbal and nonverbal interactions with its user and peripheral sensing that is more related to contextual plausibility such as sensing room temperature to empathize with the feelings of its user.…”
Section: Multisensorial Awareness For Social Companions In Augmented ...mentioning
confidence: 99%
“…A virtual human can ask or suggest the user to turn on the light or to move a real object in their proximity so that they can perform a task more plausibly. As mentioned in [44], it can do so without revealing its functional deficiency. In that paper, a distinction is made between a virtual human's basic sensing that focuses on situationally and socially appropriate verbal and nonverbal interactions with its user and peripheral sensing that is more related to contextual plausibility such as sensing room temperature to empathize with the feelings of its user.…”
Section: Multisensorial Awareness For Social Companions In Augmented ...mentioning
confidence: 99%
“…In their study, users reported that it was easier to talk to agents that had a visual representation. Furthermore, Kim and Welch [31] laid out implications for agents' behaviors in AR. They described how the way an agent is situated in and interacts with the world can affect a user's experience in AR; for instance, an agent that is not well integrated with its environment may decrease a user's sense of presence.…”
Section: Virtual Agents In Augmented Realitymentioning
confidence: 99%
“…A physical obstacle, a chair, was located on the way to the VH's locomotion target (see Figure ). In this situation, the VH may choose different behaviors to deal with the conflict—either requesting help from the participant to move the chair or passing “through” the physical chair in a ghost‐like fashion because the VH cannot physically manipulate the chair . Human participants' perceived social/copresence and behavioral dynamics with the VH were analyzed through both subjective questionnaires and objective behavioral data.…”
Section: Introductionmentioning
confidence: 99%